Commercially important fish biodiversity of Hail Haor with physicochemical properties and planktonic composition - Md. Monjurul Hasan; Md. Mehedi Hasan Pramanik; Md. Mozzammel Hoque; Rumana Yasmin; Ehsanul Karim; Md. Anisur Rahman; Yahia Mahmud (Academia Biology)
Hail Haor is one of Bangladesh’s most prominent natural freshwater wetlands, and it is unique in that majority of its catchment is located within the country. This study concentrates on recording the biodiversity of fish species that are commercially significant in the Hail Haor, as well as their current conservation status in Bangladesh and globally. This article also contains research on physicochemical parameters and the planktonic composition of water. The physicochemical parameters of water were determined to be more or less in line with Bangladesh standards, albeit they did vary between study sites. The findings revealed the presence of 41 taxa, 35 of which were Phytoplankton and 6 were Zooplankton. Hail Haor likely contains high nutrient concentrations because there are more phytoplankton species than zooplankton groups. A total of 25 commercially important fish species were determined in seven orders, with five of them being threatened. Of the documented fish species 50% were characterized as carnivores, 42% as omnivores, and 8% as planktivores. A larger proportion of carnivorous fishes suggests a greater biomass of predatory fishes. To enhance Hail Haor management and learn more about the commercially significant fish population, longer-term research is needed.